Association Between Serum Carnosinase Concentration and Activity and Renal Function Impairment in a Type-2 Diabetes Cohort - Qiu, Jiedong; Yard, Benito A.; Krämer, Bernhard K.; van Goor, Harry; van Dijk, Peter; Kannt, Aimo (Frontiers in Pharmacology, 2022)
Introduction: Genetic studies have identified associations of carnosinase 1 (CN1) polymorphisms with diabetic kidney disease (DKD). However, CN1 levels and activities have not been assessed as diagnostic or prognostic markers of DKD in cohorts of patients with type 2 diabetes (T2D). Methods: We established high-throughput, automated CN1 activity and concentration assays using robotic systems. Using these methods, we determined baseline serum CN1 levels and activity in a T2D cohort with 970 patients with no or only mild renal impairment. The patients were followed for a mean of 1.2 years. Baseline serum CN1 concentration and activity were assessed as predictors of renal function impairment and incident albuminuria during follow up. Results: CN1 concentration was significantly associated with age, gender and estimated glomerular filtration rate (eGFR) at baseline. CN1 activity was significantly associated with glycated hemoglobin A1c (HbA1c) and eGFR. Serum CN1 at baseline was associated with eGFR decline and predicted renal function impairment and incident albuminuria during the follow-up. Discussion: Baseline serum CN1 levels were associated with presence and progression of renal function decline in a cohort of T2D patients. Confirmation in larger cohorts with longer follow-up observation periods will be required to fully establish CN1 as a biomarker of DKD.